Design and development of a knowledge discovery system in inventory management - Mitrea, Catalin (2010)
The ability to learn inductively from examples is an important feature of intelligent systems. These learning methods and algorithms, which are able to generate a model of a system using the observations (data) available, are applied in a specific domain usually with the following goals: to create a system that can carry out a task and to obtain a better understanding